History of Chronic Energy Deficiency (CED) of Pregnant Women and Stunting in Toddlers - Yuliastanti, Triani; Ambarwati, Winarsih Nur; Sulastri, Sulastri; Rahmawati, Alfiah (Qualitative and Quantitative Research Center, 2023)
Children who experience stunting in the early stages of life up to five years of age will not reach their maximum physical and mental/intelligence potential in adulthood. The problem of stunting is in the world's attention, and it is evident that one of the targets of the Sustainable Development Goals (SDGs) is to reduce cases of stunting worldwide. The purpose of this study was to determine the relationship between the history of CED in pregnant women and the incidence of stunting. This research method is analytic with a case-control retrospective approach. The sampling technique used was proportional sampling, which in this study was divided into two groups, namely 24 groups of toddlers with stunting and a control group of 24 toddlers who were not stunted in Kacangan Village, Andong District, Boyolali Regency, Indonesia. The results show a significant relationship between the history of CED during pregnancy and the incidence of stunting. It is hoped that midwives can provide counseling and monitor the nutritional status of pregnant women, bearing in mind that if the nutritional status of pregnant women is good, it can reduce the incidence of stunting in toddlers. The contribution of this research is to provide information regarding the importance of the nutritional status of pregnant women.